O arquétipo na teoria junguiana e os modelos emergente e evolucionista - Martini, Wolney (2012)
This work is a reflection regarding the concept of archetype as proposed by Jung, bearing in mind the views of archetype proposed by the evolutionary and emergent models in analytical psychology. This reflection aims at identifying possible transformations in the concept of archetype in the time span ranging from 1918 to 1958. The evolutionary and emergent models propose a reconciliation between Jung´s concept and modern theories involving the workings of the brain and evolution. The central hypothesis is that there are limitations on how much we can reconcile the archetypal theory to modern neurological and evolutionary theories, for this may disregard certain key aspects in Jung´s theory. The authors contemplated here are: Emergent Model: George Hogenson, Jean Knox and John Merchant; Evolutionary Model: Anthony Stevens, Erik Goodwyn and Alan Maloney